Mediating effect of ethical climate on the relationship of personality types and employees mindfulness - Ramos, Rowena Imelda A.; Mata, Ryan Ray M.; Nacar, Rosalie C. (Linguistics and Culture Review, 2021)
Globalization and technological advancement bring changes to the organization as well as to the behaviors of the employees. As a result, this descriptive-correlational study examined the effect of perceived ethical climate on individual differences – personality types and psychological state – mindfulness among employees. Purposive sampling was utilized to include 203 participants from different higher institutions who agreed to answer a questionnaire in google forms that were distributed through their emails. Results revealed respondents’ personality types have high levels of agreeableness, conscientiousness, and open-mindedness with moderate level of extraversion and low level of negative emotionality. Individual and organizational mindfulness of the participants were considerably very high. The participants perceived their organizations to have high level of consideration on rules, standard operating procedures and law and professional codes with moderate regard personal morality. More importantly, results of structural equation modeling established the claim that ethical climate increases the significant association of personality types to employees’ mindfulness. With the evident association of personality types and mindfulness, trainings should be provided to enhance employees’ personality and deal with possible differences. The significant mediating effect of ethical climate encourage organizational leaders to establish a work environment that uplifts employee’s morale to increase mindfulness.